Bifaciomiris gen. nov., a new genus of the subfamily Mirinae (Hemiptera: Heteroptera: Miridae), with description of two new species - Kim, Junggon; Park, Haechul; Jung, Sunghoon (Zootaxa, 2020)
A new genus, Bifaciomiris gen. nov. is described to accommodate two new species, B. koreanus sp. nov. and B. vietnamensis sp. nov. Morphological information of the new genus and new species is presented with photographs and illustrations. The need of further study on the related groups is also discussed.